Life Duration of Pediatric Patients with Cancer Enrolled on Concurrent Hospice Care: A Retrospective Decedent Study - Meaghann S. Weaver; Rachel Jalfon; Emily Zeng; Shankari Kalyanasundaram; Erica C. Kaye; Marta Salek; Brittany Cowfer; Liza-Marie Johnson; Tricia Mamer; Belinda Mandrell; Lisa C. Lindley; Deena R. Levine (Journal of Palliative Medicine, 2026)
Background: The Affordable Care Act established concurrent hospice care for children, yet access and timely referral remain limited. Pediatric oncology prognostic trajectories are variable, complicating hospice timing. Objective: To quantify survival after hospice enrollment among pediatric patients with cancer and identify characteristics associated with death ≤6 versus >6 months. Methods: Three-year retrospective decedent cohort study at a single site, including all children with cancer (0–21 years) who died while enrolled in concurrent hospice care between October 1, 2022, and October 1, 2025. Electronic health record variables were structured by Andersen’s Behavioral Model (predisposing, enabling, and need factors). Univariate tests preceded multivariable Cox proportional hazards modeling. Kaplan–Meier six-month overall survival (OS) was estimated. Results: Among 213 decedents (mean age 12.2 years), median hospice length of stay was 112 days (mean 163; range 7–801). Six-month OS after hospice enrollment was 36.6%. In adjusted analyses, an out-of-hospital do not resuscitate (hazard ratio [HR] 2.69, 95% confidence interval [CI]: 1.96–3.70), financial stressors (HR 1.40, 95% CI: 1.05–1.85), and referral by an oncologist trained before institutional palliative care establishment (HR 4.19, 95% CI 3.00–5.86) were associated with death within six months. Greater exposure to chemotherapy was associated with a modestly lower hazard (HR 0.98 per dose, 95% CI: 0.97–0.99). Several biomedical factors, including diagnoses and relapse status, were not associated with time to death after adjustment. Conclusions: The findings underscore prognostic uncertainty and the influence of enabling factors on hospice enrollment timing. The study suggests reconsideration of six-month prognostic eligibility for pediatric concurrent hospice. Health service and policy-relevant studies are warranted.